Exploring Online and In-Store Purchase Willingness: Associations With the Big Five Personality Traits, Trust, and Need for Touch - Hermes, Anna; Sindermann, Cornelia; Montag, Christian; Riedl, René (Frontiers in Psychology, 2022)
Nowadays, customers can utilize both online and in-store retail channels. Consequently, it is crucial for retailers to understand the possible drivers of retail channel selection, including customers’ personalities, degrees of trust, and touch preferences. Unfortunately, current omnichannel research only scarcely addresses the effects of personality, trust, and desire to touch a product before purchasing it on willingness to purchase and how those effects vary between online and in-store shopping. Thus, we conduct an exploratory study. Our analysis of survey data (N = 1,208)—which controls for respondents’ age, gender, and education—reveals that across both the willingness to purchase in-store and online, a higher level of trust is a significant, positive predictor. However, we also identify several channel-related differences, including that the Big Five traits of Extraversion, Agreeableness, and Conscientiousness are significantly positively related to in-store, but not online, purchase willingness. We also find that Instrumental Need for Touch (defined as goal-motivated touch that accompanies purchase intention) is positively related to in-store, but negatively related to online, purchase willingness. Finally, we highlight opportunities for future research and discuss how retail managers might enhance customer experiences in their physical and online stores.